Testing the Validity of an Internal Power Theory of Interpersonal Violence - Wagers, Shelly M. (Journal of interpersonal violence, 2021)
The assertion that the motive behind battering is “power and control” is commonly accepted. Indeed, the most commonly cited “theory” behind Batterer Intervention Programs, a primary criminal justice system response to domestic violence, is that domestic violence offenders are motivated by their need to obtain “power and control.” However, this theory has not been fully developed or empirically tested. Researchers have argued for the need to turn attention back to developing better theoretical models with clear conceptualizations and operationalizations of the power construct. Wagers articulated such a theory and introduced a “super construct” called internal power. This article seeks to further develop and empirically test Wagers’s theory. Confirmatory factor analysis is used to examine the viability of the internal power construct, and structural equation modeling is used to test the relationship between the internal power factor and self-reported interpersonal abusive behaviors. Findings indicate internal power is a viable construct that warrants further exploration and offer preliminary support for internal power theory as an explanation of intimate partner violence.